Pengaruh E-Service Quality dan E-Trust terhadap E-Loyalty dengan E-Satisfaction Sebagai Variabel Intervening (study pada pengguna aplikasi Indrive - Pratiwi, Cahyaning Indah; Suryani, Wan (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2024)
This study aims to examine the influence of electronic service quality and electronic trust on electronic loyalty through electronic satisfaction as an intervening variable among Indriver customers. The type of research used is associative with a quantitative approach. The population of the study includes 103,559 individuals residing in Medan Selayang District, and a sample of 100 customers was taken using Slovin's formula with a nonprobability sampling technique. Data were collected through a questionnaire. The analysis method employed is SmartPLS (Partial Least Square), which includes model measurement (outer model), model structure (inner model), and hypothesis testing. The results indicate that electronic service quality, electronic trust, and electronic satisfaction significantly influence electronic loyalty. Furthermore, electronic service quality and electronic trust also have a positive effect on electronic satisfaction. This study explores the effect of electronic service quality on electronic loyalty through electronic satisfaction as a mediator, as well as analyzes the influence of electronic trust on electronic loyalty with electronic satisfaction serving as an intervening variable in the context of Indriver service users.